EKSPERIMENTASI MODEL PEMBELAJARAN KOOPERATIF TIPE TAPPS DAN TSTS TERHADAP KEMAMPUAN MENYELESAIKAN SOAL CERITA MATEMATIKA DITINJAU DARI TIPE KEPRIBADIAN - Astuti, Robia; Budiyono, Budiyono; Usodo, Budi (Jurnal Pembelajaran Matematika, 2014)
Abstract: The aim of this research was to determine the effect of learning models toward the ability to solve mathematical word problem viewed from the personality types. This research used the quasi-experimental research method by 3 x 4 factorial design. The population of this research was all of the students in Grade VII of State Junior High School of Tanggamus Regency in the 2013/2014 Academic Year. The samples of the research were taken by using the stratified cluster random sampling technique. The samples consisted of 283 students, and they were divided into three groups, 96 students in TAPPS class, 95 students in TSTS class, and 92 students in direct instruction class. The data was analyzed by using analysis of variance with unbalanced cells. The results of the research showed as follows. (1) The students exposed to the TAPPS and TSTS learning models have the same ability to solve mathematical word problems. However, the students exposed to the both models have the ability to solve a better mathematical word problems than the students exposed to the direct instructional model. (2) The students with idealist type have the ability to solve a better mathematical word problems than artisan type. However, guardian type, artisan type and rational type, they have the same ability to solve mathematical word problems, as well as guardian type, idealist type and rational type, they also have the same ability to solve mathematical word problems. (3) At group of rational type, the students exposed to the TAPPS learning model have the ability to solve a better mathematical word problems than the students exposed to the direct instructional model. However, the students exposed to the TAPPS and TSTS learning models have the same ability to solve mathematical word problems, and the students exposed to the TSTS and direct instructional models have the same ability to solve mathematical word problem. At group of guardian type, artisan type, and idealist type, all models (TAPPS, TSTS, and direct instructional) have provided the same ability to solve mathematical word problems. (4) In the class that using the cooperative TAPPS learning model, rational type have the ability to solve a better mathematical word problems than guardian type, while artisan type, idealist type, and rational type, they have the same ability to solve mathematical word problems, as well as guardian type, idealist type, and artisan type, they also have the same ability to solve mathematical word problems. In the class that using the cooperative TSTS and direct instuctional models, guardian type, artisan type, idealist type, and rational type, they also have the same ability to solve mathematical word problems.Keywords: Â word problem, TAPPS, TSTS, personality type.Â